Effectiveness of nutrition counseling on blood sugar levels and adherence to dietary practices in patients with type 2 diabetes mellitus - Tika, Tika Dwita Adfar; Sepni Asmira; Yumarlina; Sri Mayada Adfar (JURNAL KESMAS DAN GIZI (JKG), 2024)
One of the management strategies for Diabetes Mellitus (DM) is through nutrition counseling to increase patients' knowledge and ability to prepare food and manage their diet to achieve optimal health. This study aims to determine the effectiveness of nutrition counseling on blood sugar levels and patient adherence to the DM type 2 diet. Quasi-experimental research design using a Non-Equivalent Control Group Design. Respondents were selected using purposive sampling, resulting in 35 respondents who met the criteria. Diet adherence is assessed based on compliance with the 3Js (quantity, type, and schedule), and blood sugar levels are measured using a glucometer. Data analysis was conducted using the Wilcoxon test. The study results showed that before nutrition counseling, the intake of nutrients was as follows: carbohydrates 268.77±96.1 grams, protein 60.69±11.97 grams, fat 61.61±20.53 grams, carbohydrates 268.77±96.1 grams, and fiber 11.40±4.57 grams. After nutrition counseling, the intake was: energy 1621.17±409.01 kcal, protein 61.36±11.61 grams, fat 56.78±25.41 grams, carbohydrates 268.77±96.12 grams, and fiber 12.92±13.82 grams. The mean adherence to food type before nutrition counseling was 0.57±0.502 and after nutrition counseling was 0.91±0.284. The mean adherence to meal schedules before nutrition counseling was 0.60±0.497 and after nutrition counseling was 0.83±0.382. The mean blood sugar level before nutrition counseling was 151.20±26.787, and after nutrition counseling, it was 136.57±26.947. The conclusion is that nutrition counseling is effective in changing blood sugar levels and adherence to the diet in patients.